Participatory Education by Local Preacherso on Knowledge, Mother's Attitude and Nutritional Information of Children - Sutrio Sutrio; Antun Rahmadi; Arie Nugroho; Rauf Tamim; Andi Eka Yunianto (Sarana Ilmu Indonesia (salnesia), 2022)
Mothers as the main caregivers of children in providing feeding practices must be based on knowledge, attitudes, and good practices. The purpose of this study was to see the effect of stunting prevention through participatory counseling regarding the application of balanced nutrition to toddlers by involving local preachers on the mother's knowledge, attitudes, and nutritional intake of stunting toddlers in the stunting locus village, Gedong Tataan district. This researchwasquasi-experimental with a pre and post-test control group design. The research subjects were 21 stunted children under five in the treatment group and 21 stunted children under five as controls.The treatmentgroup was given participatory counseling intervention involving posyandu cadresand local preachers, while the control group was given counseling about balanced nutrition by posyandu cadres. Counseling was carried out for 3 weeks in a row onthe subjects of the treatment and control groups. Wilcoxon Rank Test and Mann Whitney were used to seedifferences in each group on knowledge, attitudes, and nutrient intake. This study showed that there were significant differences in knowledge (p=0,000), attitudes (p=0,000), energy intake (p=0,008), and protein (p=0,000). Stunting prevention interventions through participatory counseling on balanced nutrition involving local preachers have proven effective in increasing mothers' knowledge and attitudes about balanced nutrition as well as the nutritional intake of stunted children under five.